Pengembangan Pembelajaran Pendidikan Agama Islam Melalui Pemanfaatan Aplikasi Tik-Tok Untuk Meningkatkan Prestasi Belajar di SMP Negeri 1 Malang - Dwi Daniyarti, Wiwi; Fandi Asy’arie, Bima; Siti Khomsiyati; Refiyana Yolanda; Ananda Nova Saraswati (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
The aims of this research are (1) to design Islamic religious education learning with supporting applications, (2) to describe the inhibiting and supporting factors in PENDIDIKAN AGAMA ISLAM learning through the Tik-Tok application. This research was conducted at SMP Negeri 1 Malang. The type used in this research is “Research and Development” (R&D). This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data collection process that researchers used in this research, included interviews, questionnaires, and documentation. The feasibility test was carried out by 6 teams of validator experts including “material experts, learning design experts, and learning media experts”, and 94 students filled out questionnaires. The results of this research show that, First, design PENDIDIKAN AGAMA ISLAM learning development products through supporting applications such as "Benime, Text Voice Free, Picsart, Kine Master, Video to MP3 Converter, and Google Drive". Meanwhile, for the assessment of 6 validators including material experts, the percentage range was 84.6%. The assessment from learning design expert validators obtained a percentage range of 83.5%. The assessment from learning media expert validators obtained a percentage range of 84.2%. Third, population factors include the relevance of learning in the digital era; creativity in learning; and forming independent student learning; it becomes easier for teachers and students to work together. Inhibiting factors are additional content that is not by the subject matter; limited video duration; audio and visual problems; and inadequate internet access.